PENGARUH PENDEKATAN OPEN-ENDED BERSTRATEGI M-RTE TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA PADA MATERI PERSEGI PANJANG - Palah, Samsul; Maulana, M.; Aeni, Ani Nur (Jurnal Pena Ilmiah, 2017)
In problem solving, the students have to need creative thinking ability that will show the creative solutions without any hesitation. An open-ended approach with M-RTE strategy is one options to improving students' creative thinking ability. The research uses quasi experiment method with nonequivalent control group design. Research population is all students of grade V SD in North Sumedang Subdistrict. Meanwhile, the samples are SDN Bendungan 2 as the experimental class and SDN Sukamulya as the control class. After learning during four times, both at SDN Bendungan 2 or SDN Sukamulya have increased on mathematical creative thinking ability. Hence the open-ended approach with M-RTE strategy and conventional approach have a positive effect on mathematical creative thinking ability. However, based on the average of N-gain obtained there is no a significant difference between the positive effects of the open-ended approach with M-RTE strategy and the conventional approach.Â